HUBUNGAN ANTARA INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN BODY DISSATISFACTION PADA MAHASISWA DI DAERAH ISTIMEWA YOGYAKARTA - Sudiani, Bai; Ariyanto, Mustaqim Setyo (Jurnal Riset dan Inovasi Pembelajaran, 2023)
This research aims to test and explain the relationship between the intensity of social media use and body distatisfaction. The respondents in this research were 110 students including women and men in the Special Region of Yogyakarta. Sampling was carried out using Incidental Sampling and Snowball Sampling techniques. The instruments used were the multiple body-self related questionnaire appearance scales (MBSRQ-AS) and the intensity scale of social media use. The data analysis technique used is Pearson product moment correlation. The results of data analysis obtained a value of r = 0.423 with p = 0.001 (p < 0.01) indicating that there is a significant relationship between the intensity of social media use and body dissatisfaction. Based on the results of the research and discussion, it can be seen that there is a significant relationship between the intensity of social media use and body dissatisfaction among students in the Special Region of Yogyakarta. Therefore, unproductive use of social media should be avoided to avoid body statisfaction and increase student productivity as agents of future change.